Vaginal Progesterone Is Associated with Intrahepatic Cholestasis of Pregnancy - Tsur, Abraham; Leonard, Stephanie A.; Kan, Peiyi; Datoc, Imee A.; Girsen, Anna I.; Shaw, Gary M.; Stevenson, David K.; El-Sayed, Yasser Y.; Druzin, Maurice L.; Blumenfeld, Yair J. (American Journal of Perinatology, 2023)
Objective The frequency of intrahepatic cholestasis of pregnancy (ICP) peaks during the third trimester of pregnancy when plasma progesterone levels are the highest. Furthermore, twin pregnancies are characterized by higher progesterone levels than singletons and have a higher frequency of cholestasis. Therefore, we hypothesized that exogenous progestogens administered for reducing the risk of spontaneous preterm birth may increase the risk of cholestasis. Utilizing the large IBM MarketScan Commercial Claims and Encounters Database, we investigated the frequency of cholestasis in patients treated with vaginal progesterone or intramuscular 17α-hydroxyprogesterone caproate for the prevention of preterm birth.Study Design We identified 1,776,092 live-born singleton pregnancies between 2010 and 2014. We confirmed second and third trimester administration of progestogens by cross-referencing the dates of progesterone prescriptions with the dates of scheduled pregnancy events such as nuchal translucency scan, fetal anatomy scan, glucose challenge test, and Tdap vaccination. We excluded pregnancies with missing data regarding timing of scheduled pregnancy events or progesterone treatment prescribed only during the first trimester. Cholestasis of pregnancy was identified based on prescriptions for ursodeoxycholic acid. We used multivariable logistic regression to estimate adjusted (for maternal age) odds ratios for cholestasis in patients treated with vaginal progesterone, and in patients treated with 17α-hydroxyprogesterone caproate compared with those not treated with any type of progestogen (the reference group).Results The final cohort consisted of 870,599 pregnancies. Among patients treated with vaginal progesterone during the second and third trimester, the frequency of cholestasis was significantly higher than the reference group (0.75 vs. 0.23%, adjusted odds ratio [aOR]: 3.16, 95% confidence interval [CI]: 2.23–4.49). In contrast, there was no significant association between 17α-hydroxyprogesterone caproate and cholestasis (0.27%, aOR: 1.12, 95% CI: 0.58–2.16)Conclusion Using a robust dataset, we observed that vaginal progesterone but not intramuscular 17α-hydroxyprogesterone caproate was associated with an increased risk for ICP.Key Points
Keywords: preterm birth; 17α-hydroxyprogesterone caproate; micronized progesterone; claims